2013
DOI: 10.1113/jphysiol.2012.242719
|View full text |Cite
|
Sign up to set email alerts
|

Interventricular comparison of the energetics of contraction of trabeculae carneae isolated from the rat heart

Abstract: Key points• With each beat of the heart, the left and right ventricles must overcome substantially different arterial pressures in order to eject blood.• We have tested whether this difference in mechanical demand is reflected in different metabolic energy expenditure.• Our experimental preparations were trabeculae isolated from both ventricles; our index of metabolic energy expenditure was their heat production in response to electrical stimulation.• We found that the cost of activating contraction (i.e. the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 103 publications
5
28
0
Order By: Relevance
“…One of the reasons for this observation is the reference to the "muscle elongation work", which is defined as the product of the force and the displacement as "work", without accounting for all the other types of work that a cell has to perform, such as pumping ions from a low concentration zone to a high concentration zone, synthesizing enzymes etc., which is only a fraction of the total work done by the cell. This situation is evidenced by Han et al (2013), who reported that 35% greater maximum mechanical efficiency of the right ventricular muscle is offset by the greater metabolic cost of activation of the left ventricular trabeculae, when work is calculated in terms of the shortening velocity and power. Different experimental protocols and temperatures are used in most of the previous studies; exclusion of the energy expenditure for pumping the ions from the efficiency calculations is usually achieved on purpose during the design of the experiments (Barclay and Weber 2004).…”
Section: Comparison Of the Theoretical Limits With The Calculations Bmentioning
confidence: 83%
See 1 more Smart Citation
“…One of the reasons for this observation is the reference to the "muscle elongation work", which is defined as the product of the force and the displacement as "work", without accounting for all the other types of work that a cell has to perform, such as pumping ions from a low concentration zone to a high concentration zone, synthesizing enzymes etc., which is only a fraction of the total work done by the cell. This situation is evidenced by Han et al (2013), who reported that 35% greater maximum mechanical efficiency of the right ventricular muscle is offset by the greater metabolic cost of activation of the left ventricular trabeculae, when work is calculated in terms of the shortening velocity and power. Different experimental protocols and temperatures are used in most of the previous studies; exclusion of the energy expenditure for pumping the ions from the efficiency calculations is usually achieved on purpose during the design of the experiments (Barclay and Weber 2004).…”
Section: Comparison Of the Theoretical Limits With The Calculations Bmentioning
confidence: 83%
“…The muscle work efficiencies listed in Table 3 are subject to variance and may change even in the different muscles of the same organism depending on their biological properties: Han et al (2013) reported 35% greater maximum mechanical efficiency of the rat right ventricular muscle than that of the left ventricular trabeculae. The muscle work efficiency may vary with time even in the same muscle: Barclay and Weber (2004) after determining the work output and heat production in in vitro experiments with the slowtwitch soleus and fast-twitch extensor digitorum longus muscle fibers from mouse reported that during the first second of the experiments the efficiency was greater in the slow-twitch soleus muscle, than it was in the fast-twitch extensor digitorum longus muscle, but there was no difference in the net efficiency of the muscles in the longer time span.…”
Section: Comparison Of the Theoretical Limits With The Calculations Bmentioning
confidence: 99%
“…Whereas there was no difference in mechanical performance, the elevated activation heat of specimens from the left ventricle rendered their contractile performance less efficient (66). More recent studies have shown that streptozotocin-induced type I diabetes has no effect on the energetic performance of ventricular trabeculae (70) despite causing the peak efficiency of the isolated whole heart to shift to lower values of afterload (62).…”
Section: Cardiac Muscle Myometrymentioning
confidence: 99%
“…Studies of force production simultaneous with heat output of cardiac muscle require the use of isolated tissue preparations such as small papillary muscles (2-4, 12, 26, 34) or trabeculae carneae (17)(18)(19)(20)(21) as they are sufficiently small to avoid muscle anoxia (14). The use of these tissue preparations, which have approximately one-dimensional arrangements of myocytes, simplifies the interpretation of measurements.…”
Section: We Have Developed a New Muscle Calorimeter Which Has Enablementioning
confidence: 99%